Analisis Biaya dan Waktu Pembangunan Dinding Penahan Tanah pada Proyek Pembangunan Drainase Utama dan Revitalisasi Drainase Utama Kota Jambi - Resa Utami; Harmes Harmes; Putri Nurul Kusuma Whardani (International Forum of Researchers and Lecturers, 2026)
The development and revitalization of the Sungai Asam drainage system in Jambi City face serious problems in the form of river sedimentation and limited channel capacity, which trigger flooding. These conditions necessitated a design change for bank protection from revetment to a retaining wall (Dinding Penahan Tanah/DPT) in the SA223 to SA228 segment. This study aims to analyze the construction cost and implementation duration of the DPT resulting from the design change. The theoretical framework covers retaining wall concepts, cost estimation (Bill of Quantities), and construction project scheduling. A descriptive-analytical method was applied using secondary data, including design drawings, work volumes, the 2025 Water Resources and Human Settlements Unit Price Analysis (AHSP), the 2025 Jambi Provincial Standard Unit Prices, and time analysis using the S-Curve and Critical Path Method (CPM). The results indicate that the total construction cost of the DPT in the SA223–SA228 segment is IDR 9.524.259.092,02, while the project duration is determined based on the critical path identified through CPM analysis. The discussion confirms that the design change significantly affects work complexity, construction costs, and schedule adjustments. The study concludes that systematic and measurable cost and time analyses are essential as a technical basis for decision-making in river revitalization projects to ensure effectiveness, efficiency, and the sustainability of flood control infrastructure.